Technology leaps in quantum sensing: Advances in nano magnetometry using tailored electronics and fast‐switchable lasers. Issue 4 (4th August 2021) - Waasem, Niklas; Fedder, Helmut; Maletinsky, Patrick
Abstract: Taking advantage of quantum effects has enabled the so‐called first quantum revolution in the 20th century for technologies such as nuclear magnetic resonance spectroscopy, magnetic resonance imaging, and the development of transistors, LEDs, solar panels, and lasers.